Pragmalinguistic analysis of the peruvian electoral debate: The case of Fernando Olivera and Alan García - Pérez Taype, Sindy (2021)
This study analyzes the electoral debate of 2016, specifically the confrontation between the candidates Fernando Olivera and Alan García. It was decided to work with this corpus, since a contrast is evident in the pragmalinguistic strategies used by both candidates; therefore, the main objective is to demonstrate each of these strategies. In the first part of the study, the content of the political discourse of both candidates is analyzed, for this the functional theory proposed by William Benoit (2007) is used. Based on this analysis, the second part describes the pragmalinguistic resources present in the speeches of each one of them. It is concluded that both candidates present differences in the content of their message: while Fernando Olivera’s speech has a denigrating propensity, Alan García has a propensity for silence. Likewise, the most widely used pragmalinguistic resources are verbal discourtesy and personal deixis.